Study on the Influencing Factors of Chinese Students Attending Private High Schools - Li, Yuelin (Transactions on Social Science, Education and Humanities Research, 2024)
After the official implementation of China’s ‘General Employment Diversion’ policy on high school entrance examination, only about 50 percent of students will win the competition for senior high school education while the rest will enter vocational schools. This policy has led to the trend of parents choosing private high schools in China. Based on a detailed explanation of the general employment diversion policy, this paper analyzes the factors that affect Chinese parents’ choice of private high schools and vocational schools by integrating three representative cases through interview analysis, and analyzes the family and social conflicts caused by the general employment diversion policy from a multi-dimensional perspective, as well as possible solutions. Through the reference of the existing research results of the general employment diversion policy and the interview of three cases, Chinese parents with different economic conditions are more inclined to choose high school education, which leads to the competition of educational resources in private high schools, as well as family conflicts and economic burdens. To standardize and improve the teaching and management of private high schools and vocational schools, and to change the cognitive limitations of public opinion on vocational education are crucial to realizing the equity of high school education.